Tunable nonenzymatic degradability of N-substituted polyaspartamide main chain by amine protonation and alkyl spacer length in side chains for enhanced messenger RNA transfection efficiency. Issue 1 (1st January 2019) - Naito, Mitsuru; Otsu, Yuta; Kamegawa, Rimpei; Hayashi, Kotaro; Uchida, Satoshi; Kim, Hyun Jin; Miyata, Kanjiro
ABSTRACT: Degradability of polycations under physiological conditions is an attractive feature for their use in biomedical applications, such as the delivery of nucleic acids. This study aims to design polycations with tunable nonenzymatic degradability. A series of cationic N -substituted polyaspartamides were prepared to possess primary amine via various lengths of alkyl spacers in side chains. The degradation rate of each polyaspartamide derivative was determined by size exclusion chromatography under different pH conditions. The N -substituted polyaspartamide containing a 2-aminoethyl moiety in the side chain (PAsp(AE)) showed considerable degradability under physiological conditions (pH 7.4, 37 °C). In contrast, the N -substituted polyaspartamides bearing a longer alkyl spacer in the side chain, i.e. the 3-aminopropyl (PAsp(AP)) and 4-aminobutyl moieties (PAsp(AB)), more strongly suppressed degradation. Further, a positive correlation was observed between the degradation rate of N -substituted polyaspartamides and a deprotonation degree of primary amines in their side chains. Therefore, we conclude that the deprotonated primary amine in the side chain of N -substituted polyaspartamides can induce the degradation of the main chain through the activation of amide nitrogen in the side chain. When N -substituted polyaspartamides were utilized as a messenger RNA (mRNA) delivery vehicle via formation of polyion complexes (PICs), degradable PAsp(AE) elicited significantly higher mRNA expression efficiency in cultured cells compared to PAsp(AP) and PAsp(AB). The higher efficiency of PAsp(AE) might be due to the facilitated destabilization of PICs within the cells, directed toward mRNA release. Additionally, degradation of PAsp(AE) considerably reduced its cytotoxicity. Thus, our study highlights a useful design of well-defined cationic poly(amino acid)s with tunable nonenzymatic degradability. Graphical abstract: